Cardiac imaging - White, Charles S.; Haramati, Linda B.; Chen, Joseph Jen-Sho; Levsky, Jeffrey M. ([Oxford] : Oxford University Press, 2014)
Based on the learning goals of the Society of Thoracic Radiology Curriculum in Cardiac Radiology,'Cardiac Imaging' presents core knowledge that must be learned to accurately and effectively interpret cardiac imaging studies. This book imparts essential facts about all imaging modalities and the basics of interpretation and technique in a concise and readable format.
Previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 23, 2016).
Keywords: Heart -- Imaging